Highly-interpenetrated and phase-separated UV-cured interpenetrating methacrylate–epoxide polymer networks: Influence of the composition on properties and microstructure. (March 2016) - Rocco, C.; Karasu, F.; Croutxé-Barghorn, C.; Allonas, X.; Lecompère, M.; Riess, G.; Zhang, Y.; Esteves, A.C.C.; van der Ven, L.G.J.; van Benthem, R.A.T.M.; de With, G.
Graphical abstract: Highlights: Monomers miscibility and synthesis parameters control the IPN formation. Miscibility investigations are used to predict final morphology of UV-cured films. RT-FTIR, DMA, AFM and AFAM characterizations corroborate miscibility predictions. Different morphologies are obtained depending on IPN composition. AFAM gives precise results on surface elasticity, without topography effects. Abstract: Interpenetrating Polymer Networks (IPNs) based on a polybutadiene dimethacrylate and a dicyclohexylepoxide mixed at different ratios have been synthesized by photopolymerization. To obtain a complete overview of the formation and phase separation of these IPNs, and to predict the final morphology, miscibility before and after polymerization has been studied. By varying the methacrylate/epoxide ratio, it was possible to move from a miscible and highly-interpenetrated system to a totally immiscible and phase-separated one. Miscibility effects on the polymerization kinetics of both polymer networks, final properties and surface morphology were investigated by RT-FTIR, DMA, AFM and AFAM. This overall characterization gives a better understanding of the formation and phase separation process in this system, depending on the mixture composition.